Between Multiple Identities and Values: Professionals’ Identity Conflicts in Ethically Charged Situations - Carminati, Lara; Héliot, YingFei Gao (Frontiers in Psychology, 2022)
This study explored identity conflict dynamics in interpersonal interactions in professionals facing ethically-charged situations. Through semi-structured interviews (N=47), we conducted a qualitative study among doctors and nurses working for the English National Healthcare Service and analyzed the data with grounded theory approaches. Our findings reveal that identity conflict is triggered by three micro processes, namely cognitive and emotional perspective taking, as well as identifying with the other. In these processes, identity conflict is signaled by emotions and recognized as a clash not only between identities and their values, but also within one identity and its multiple values. Behavioral and psychological outcomes of identity conflict involve seeking peer support, doing reflective practices and identity growth. This article contributes to identity literature by providing a multilevel approach of identity conflict dynamics able to account for both interpersonal and intrapsychic processes, deeply-hold values and emotions, as well as crucial behavioral and psychological consequences.